The effect of cervical spondylosis on diaphragmatic thickness and excursion in nonsmoking adults - Bishoy G Khalil; Akram A Elaziz; Tamer A El-Kassas; Saif Mehmed (Journal of Medicine in Scientific Research, 2021)
Background Cervical spondylosis is defined as a series of signs and symptoms that result in anatomical and physiological changes in the vertebral column that may impair phrenic nerve function by compressing the C3/C5 that affect diaphragmatic movements. Purpose The purpose of this study was to investigate the effect of cervical spondylosis on diaphragmatic thickness and excursion in nonsmoking adults by using ultrasonographic evaluation of the diaphragm. Eighty-four nonsmoking volunteers participated in this study and were divided into two equal groups: group A, patients with cervical spondylosis and group B, healthy volunteers with a normal cervical spine. Both groups were evaluated by the same methods. Results The results f this study showed that there was a statistically significant decrease (P < 0.05) in diaphragmatic thickness, diaphragmatic rest, and deep-excursion means in favor of group A compared with its corresponding value in group B. Conclusion The present study revealed that the cervical spondylosis has an effect on diaphragmatic thickness and excursion in nonsmoking adults.